Extrinsic induction of apoptosis and tumor suppression via the p53–Reprimo–Hippo–YAP/TAZ–p73 pathway - Masahiro Takikawa; Airi Nakano; Jayaraman Krishnaraj; Yuko Tabata; Yuzo Watanabe; Atsushi Okabe; Yukiko Sakaguchi; Ryoji Fujiki; Ami Mochizuki; Tomoko Tajima; Akane Sada; Shu Matsushita; et al. (Proceedings of the National Academy of Sciences, 2025)
Tumor progression is suppressed by inherent cellular mechanisms such as apoptosis. The p53 tumor suppressor gene is the most commonly mutated gene in human cancer and plays a pivotal role in tumor suppression. RPRM is a target gene of p53 known to be involved in tumor suppression, but its molecular function has remained elusive. Here, we report that Reprimo (the protein product of RPRM ) is secreted and extrinsically induces apoptosis in recipient cells. We identified FAT1, FAT4, CELSR1, CELSR2, and CELSR3, members of the protocadherin family, as receptors for Reprimo. Subsequent analyses revealed that Reprimo acts upstream of the Hippo–YAP/TAZ–p73 axis and induces apoptosis by transactivating various proapoptotic genes. In vivo analyses further support the tumor-suppressive effects of secreted Reprimo. These findings identify the p53–Reprimo–Hippo–YAP/TAZ–p73 axis as an extrinsic apoptosis pathway that plays a crucial role in tumor suppression. Our finding of the innate tumor eliminator Reprimo and the downstream pathway offers a promising avenue for the pharmacological treatment of cancer.